2007
DOI: 10.1002/ajim.20516
|View full text |Cite
|
Sign up to set email alerts
|

On the job illness and injury resulting in lost work time among a national cohort of emergency medical services professionals

Abstract: Results from this analysis provide estimates of the prevalence and incidence of on the job illness and injury resulting in lost work time among a national cohort of EMS professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 29 publications
1
19
0
3
Order By: Relevance
“…Taking the severity of injury (measured by lost work time) into account, the prevalence of an injury with lost work time in our study (2.9%) was lower than that of surveyed EMTs (9.5%). 30 However, we do not know if this is because ATs experienced fewer severe injuries compared with EMTs, successfully modified their work tasks, or had less ability to take time off work.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the severity of injury (measured by lost work time) into account, the prevalence of an injury with lost work time in our study (2.9%) was lower than that of surveyed EMTs (9.5%). 30 However, we do not know if this is because ATs experienced fewer severe injuries compared with EMTs, successfully modified their work tasks, or had less ability to take time off work.…”
Section: Discussionmentioning
confidence: 99%
“…3,16,[40][41][42][43][44][45][46] This lack of standardization hinders the measurement of injuries to EMS providers, and makes it difficult to systematically evaluate and re-duce such injuries. In addition, existing data are rarely shared outside of a single EMS agency or jurisdiction.…”
Section: Host Factor Solutionsmentioning
confidence: 99%
“…5,6 In the execution of these duties, paramedics may be required to perform physically demanding tasks or be exposed to occupational hazards, which can potentially lead to morbidity or mortality. [7][8][9][10] Research has indicated that there are relatively high levels of occupational injury and illness associated with the paramedic profession. 1,4,7,8,[11][12][13][14] Ideally, paramedics would have a high standard of fitness to enable a prompt response for emergency health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Occupational injury can produce physical, social, and economic impacts on the individual, workforce, and the community. 3,7,9,19,20 Accordingly, improving the fitness of all paramedics has the potential to modify and reduce the risk of occupational injury or illness in the future.…”
Section: Introductionmentioning
confidence: 99%